EXPLORING FAMILY-BASED ENGLISH LANGUAGE ACQUISITION IN DAILY LIFE: A NARRATIVE INQUIRY - El-Hamziyah, Millatul Fitriyah; Ferdiyanto, Feri; Islam, Raudhatul (International Journal of Research on English Teaching and Applied Linguistics, 2025)
Family-based English language learning gained attention as an alternative to formal education, yet limited research explored its practical implementation. Discrepancies existed between theoretical models of language acquisition and how families applied them at home. This study aimed to investigate how interactive learning strategies within a family environment supported English language development. Using a narrative inquiry approach focused on one multilingual family, this research explored daily practices and challenges encountered. Findings revealed that engaging in daily English conversations, utilizing multimedia, fostering self-directed learning, offering emotional support, and promoting a growth mindset significantly enhanced language acquisition. These practices reflected major theories such as Vygotsky’s Zone of Proximal Development, Mayer’s Multimedia Learning Theory, Benson’s Self-Directed Learning Framework, Krashen’s Affective Filter Hypothesis, and Dweck’s Growth Mindset Theory. Challenges included limited parental proficiency, time constraints, learner motivation fluctuations, technology access issues, and the need for careful error correction. The study concluded that family involvement, even without formal training, successfully bridged theoretical and practical gaps in language learning. Further research was recommended to examine diverse family settings and develop intervention programs to strengthen family-based learning.